2023
DOI: 10.3390/ani13071141
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Amino Acid Metabolism and Bovine In Vitro Follicle Activation and Growth

Abstract: The amino acid metabolism of bovine follicles during in vitro growth (IVG) was evaluated to identify potential indicators of health during culture. The bovine ovarian cortex was sliced, prepared as strips, and cultured for 6 days. Tissue samples were examined histologically before and after 6 days of culture, and the degree of follicle activation was classified as either high or low based on the number of growing secondary follicles present (high: 7~11; low: 0~1). In a separate experiment, secondary follicles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…After centrifugation (9,600 × g ) at 4°C for 15 min, the supernatant was collected and diluted five-fold with 0.02 M HCl. Free amino acids were analyzed using an automatic amino acid analyzer (L-8900; Hitachi, Tokyo, Japan) as previously described [ 31 ]. The list of molecular species and their abbreviations detected by the amino acid analyzer are described below.…”
Section: Methodsmentioning
confidence: 99%
“…After centrifugation (9,600 × g ) at 4°C for 15 min, the supernatant was collected and diluted five-fold with 0.02 M HCl. Free amino acids were analyzed using an automatic amino acid analyzer (L-8900; Hitachi, Tokyo, Japan) as previously described [ 31 ]. The list of molecular species and their abbreviations detected by the amino acid analyzer are described below.…”
Section: Methodsmentioning
confidence: 99%
“…In in vitro studies, it was observed that follicular cultivation with the addition of amino acids such as arginine, lysine, and methionine enabled the activation of primordial ovarian follicles in bovines, as observed by Sakaguchi et al (2023). This effect may be related to the inhibition of the homologous tensin and phosphatase pathways (PTEN), which are the main negative regulators of phosphoinositide 3-kinase (PI3K), thus contributing to the perpetuation of dormancy in primordial follicles.…”
Section: Reproductive Responsementioning
confidence: 96%
“…Sakaguchi et al [39] investigated the metabolism of amino acids (which assume diverse roles such as protein synthesis, sources of energy and osmotic pressure, and pH adjustment for cell cultures [40]) during IVG to find non-invasive bio markers to predict the health status of follicles. They found possible molecular species that could be the marker for both cortical strip culture for primordial follicular activation (methionine, lysine, arginine, and α-aminoadipic acid) and IVG for secondary follicles (methionine, tyrosine, histidine, and hydroxyproline).…”
mentioning
confidence: 99%
“…In conclusion, this Special Issue covers culture systems from a wide range of follicular developmental stages, including primordial follicles [39], secondary follicles [35,39], early antral follicles [31], small antral follicles [41], in vivo grown antral follicles [35], and whole ovarian cultures [37]. Moreover, it consists of studies of four different species, including water buffaloes [31], cattle [33,35,39], mice [37], and pigs [39].…”
mentioning
confidence: 99%
See 1 more Smart Citation